Could we stimulate melatonin secretion through Tahajjud? - akram heidari; Ali Fattahi Bafghi; Sayyed Ziaadin Tabeaie; Reza Bani- Asadi; Mohammad afkhami Ardakani; Kazem Barzegar; mahmood vakili; morteza heidari (Journal of Kerman University of Medical Sciences)
Background: Islamic instructions suggest waking up near dawn at night and spending time praying to Allah. This is the time of maximum melatonin secretion, that is a hormone mainly functioning in the circadian rhythm. Melatonin secretion declines with age and leads to different clinical consequences. This study aimed to investigate the melatonin levels among night vigil prayers, non-prayer late sleepers, and those with regular night sleep.Methods: A questionnaire including information about age, gender, education, and occupation was used to collect the demographic information of the participants. Melatonin was measured with two blood draws (at 23:00 to 24:00 and 9:00 to 10:00 a.m.). Results: There was a significant difference between both nocturnal and daily melatonin of the night vigil prayers with the other two groups. The average daily melatonin serum level had no significant difference in groups of regular night sleepers and the nonpraying late sleepers (p=0.306). Moreover, an adverse significant relationship was found between age and nocturnal melatonin (R=0.38, P<0.0001) and between age and daily melatonin (R=0.25, P=0.02).Conclusion: The night vigil prayers have a higher average of nocturnal and daily melatonin serum secretion compared to the nonpraying late sleepers and regular night sleepers. Therefore, waking up at night accompanied by approaching Allah, prayer, supplication, and good thinking is related to the release of more melatonin.